Linearity, symmetry, and equidistance in semantic differential scales for measuring images of self and images of others. Issue 2 (3rd April 2018) - Eifler, Stefanie; Menold, Natalja
ABSTRACT: Violations of linearity, symmetry, and equidistance of scale points in semantic differential scales may be due to respondents failing to figure out antonyms, to a positivity bias, or to respondents curtailing their reading the options. Multiple correspondence analysis on data provided by a randomized between-subjects experiment (split-ballot), using a web survey of 537 German residents, shows that bipolar semantic differential scales allow for linear measurement and conceal no positivity bias, and that using not suitable adjective pairs in semantic differential scales destroys symmetry.